Fear of Covid-19 Scale: : An Exploratory Study among Young People in Higher Education Institutions - Dadang Munandar; Umi Narimawati; Nabiha Khan; Manan Sailan; Mohsin Mohsin (International Journal of Educational Administration, Management, and Leadership, 2022)
This study explores some empirical validity of the fear of the Covid-19 scale. The study intends to examine potential validity when the scale is used for young people attending higher education institutions in Indonesia. Researchers invited undergraduate students from five universities in Indonesia. Four hundred fourty five participants fully completed the survey within six weeks of data collection. The study was conducted online through an online survey platform where most participants completed the survey within 20 minutes. Two measures were employed, the fear of Covid-19 and the perceived stress scale. The results supported the theoretical measurement model in which fear of Covid-19 and perceived stress scale each represented a unidimensional construct. The Principal Component Analysis (PCA) also found that the fear of the Covid-19 scale generated positive loading factors for its items with an average variance extracted (AVE) higher than 50%. The Pearson's correlation's predictive validity study observed a positive and significant association between fear of Covid-19 and perceived stress. This study has provided initial empirical support for the use of fear of Covid-19 for young people who attend higher education institutions. The fear of the Covid-19 measure was also in line with several studies and the Conservation of Resource theory. People who perceive crisis will experience threats to their resources, and they will be more likely to experience stress if they do not have enough resources to cope with the threats.